Changing Corporate Governance in Response to Negative Media Reports. (6th July 2018) - Okhmatovskiy, Ilya; Shin, Donghoon
Abstract: We study how organizations change their corporate governance in response to negative publicity in the media. We build on insights from the literature on interpersonal trust to theorize how organizations respond to different types of trust‐damaging information. We suggest that organizations are likely to replace key individuals involved in the corporate governance process when trust‐damaging information provides evidence of low integrity. In contrast, organizations are likely to make changes in how the governance process is organized when trust‐damaging information provides evidence of low benevolence. We test our hypotheses by using data on publicly traded Korean firms from 2006 to 2013. Our results provide general support for our argument about corporate governance changes that organizations initiate in response to different types of trust‐damaging information. We also explore how foreign ownership and state ownership moderate organizational responses to trust‐damaging information.